Validation of the burnout assessment tool-core symptoms in Spanish veterinarians, sex invariance, and cutoff points - Osca, Amparo; Barrado, Jesús; Millán, Lorena (Frontiers in Veterinary Science, 2024)
Notably, most studies on burnout in Veterinary Medicine have used the Maslach Burnout Inventory; however, it has limitations and does not evaluate severe burnout. Therefore, in this study, we validated the Burnout Assessment Tool-Core Symptoms (BAT-C) in a sample of Spanish veterinarians. Its invariance concerning sex and cutoff points were also calculated using the receiver operating characteristic curve analysis and Youden’s index. The sample included 1,215 Spanish veterinarians (70% women). The analyses confirmed that the BAT-C evaluates four dimensions: exhaustion (eight items), mental distance (five items), emotional impairment (five items), and cognitive impairment (five items). Reliability analyses offered adequate results, and the high correlation of the BAT-C with a measure of work stress demonstrates its criterion validity. The invariance analyses showed that it evaluates psychometric guarantees, regardless of the sex of the veterinarian. Regarding the cutoff points, there were more women than men in the high (36.9% vs. 25.5%) and medium (22.4% vs. 18.6%) burnout groups and fewer women in the low burnout group (40.7% vs. 55.9%). Our results support the Spanish version of the BAT-C as a valid instrument to assess the core symptoms of severe burnout among veterinarians. Based on our findings, we provide some practical recommendations to reduce burnout in veterinarians.